Measuring the expansion and age of the nova shell IPHASX J210204.7 + 471015. Issue 3 (18th December 2018) - Santamaría, E; Guerrero, M A; Ramos-Larios, G; Sabin, L; Vázquez, R; Gómez-Muñoz, M A; Toalá, J A
ABSTRACT: The parallax expansion and kinematics of a nova shell can be used to assess its age and distance, and to investigate the interaction of the ejecta with the circumstellar medium. These are key to understand the expansion and dispersal of the nova ejecta in the Galaxy. Multi-epoch images and high-dispersion spectroscopic observations of the recently discovered classical nova shell IPHASX J210204.7 + 471015 around a nova-like system have been used to derive a present-day expansion rate of 0${^{′′}_{.}}$ 100 yr −1 and an expansion velocity of 285 km s −1 . These data are combined to obtain a distance of 600 pc to the nova. The secular expansion of the nova shell place the event sometime between 1850 and 1890, yet it seems to have been missed at that time. Despite its young age, 130–170 yr, we found indications that the ejecta has already experienced a noticeable deceleration, indicating the interaction of this young nova shell with the surrounding medium.